Natural course of mild cognitive impairment in Parkinson disease: A 5-year population-based study. (21st February 2017) - Pedersen, Kenn Freddy; Larsen, Jan Petter; Tysnes, Ole-Bjørn; Alves, Guido
Abstract : Objective: To examine the incidence, progression, and reversion of mild cognitive impairment in patients with Parkinson disease (PD-MCI) over 5 years. Methods: A population-based cohort of patients with incident PD underwent repeated neuropsychological testing of attention, executive function, memory, and visuospatial abilities at baseline (n = 178), 1 year (n = 175), 3 years (n = 163), and 5 years (n = 150). Patients were classified as PD-MCI and diagnosed with dementia according to published criteria. Results: Thirty-six patients (20.2%) fulfilled criteria for PD-MCI at baseline. Among those with normal cognition at baseline (n = 142), the cumulative incidence of PD-MCI was 9.9% after 1 year, 23.2% after 3 years, and 28.9% after 5 years of follow-up. Overall, 39.1% of patients with baseline or incident PD-MCI progressed to dementia during the 5-year study period. The conversion rate to dementia was 59.1% in patients with persistent PD-MCI at 1 year vs 7.2% in those with normal cognition during the first year (adjusted odds ratio 16.6, 95% confidence interval 5.1–54.7, p < 0.001). A total of 27.8% of patients with baseline PD-MCI and 24.2% of those with incident PD-MCI had reverted to normal cognition at study end, but the reversion rate decreased to 9.4% in those with persistent PD-MCI at 2 consecutive visits. Compared with cognitively normal patients, PD-MCI reverters within the first 3 years of follow-up were at increased risk of subsequently developing dementia (adjusted odds ratio 10.7, 95% confidence interval 1.5–78.5, p = 0.019). Conclusions: Early PD-MCI, regardless of persistence or reversion to normal cognition, has prognostic value for predicting dementia in patients with PD.